The Influence Knowledge Management on Marketing Performance - Ade Ilham Pratama; Syahputra Syahputra (Almana : Jurnal Manajemen dan Bisnis, 2020)
FPS Famous Pacific Shipping is a company engaged in the field of the expedition which was formed in 2006, the company began with the name Internusa Hasta Buana which was founded by Mr. Iskandar Zulkarnain in 1991. Internusa Hasta Buana then gave birth to a subsidiary namely FPS Indonesia (Famous Pacific Shipping). This research aims to determine the influence of knowledge management on marketing performance at PT. FPS Indonesia. The variables used in this study are Knowledge Management (X1), and dependent variable (Y), Marketing Performance. The research method used is a quantitative method with descriptive and causal research types. The unit of analysis is a total sample of 20 employees of PT. FPS Indonesia. The data collection method was carried out through questionnaires containing 20 valid questions. The analysis technique uses simple linear regression and the data is calculated using the SPSS program. Based on the calculation of the coefficient of determination shows a value of 59.8% which means this value indicates that the Knowledge Management variable has an influence on Marketing Performance of 59.8% and the remaining 40.2% is influenced by variables not examined.